THE RELATIONSHIP OF WORK ENVIRONMENT TOWARDS EMPLOYEE’S JOB SATISFACTION FOR MILLENNIALS IN JAKARTA - Wicaksono, Dimas Fauzi; Pritasari, Adita (Journal of Business and Management, 2018)
Abstract. The objective of this study is to find out what factors affect employee work satisfaction and what factors are the most dominant drivers of each generation of work. Focusing on Generation X and Generation Y as the most dominant generation in a company, this research will measure the level of employee work satisfaction in PT PP in Jakarta. This research is supported by the theory of Herzberg Two Factors Theory and Job Characteristic Model chosen to assist the researcher in conducting the analysis of this research data. Using quantitative methods, the researcher distributed questionnaires to employees at PT PP Jakarta to assess the level of job satisfaction indicator. The results obtained from this study are the dominant factors from each generation are different, the promotion of work for generation X and the salary for generation Y.Keywords: Generation X, Generation Y, Job Satisfaction, Working Generation, Motivation Factor